Green production innovation and green craft innovation effects on relationship between environmental corporate social responsibility and corporate value in China - Ao, Xiangyuan (2022)
Since the introduction of increasingly strict environmental protection laws in China, organisations and corporations have attached great importance to it. Encouraging companies to adhere to these stringent regulatory requirements and truly assume environmental responsibility is an urgent issue of concern to the government and companies’ board of directors. Therefore, as a solution to this urgent problem, it is particularly important to study the moderating effect of green innovation on the relationship between environmental corporate social responsibility (ECSR) and corporate value. This study adopted the theoretical bases of the stakeholder theory and resourcebased theory to, first, examine the effect of ECSR dimensions (environmental production consciousness, eco-friendly production, and green management) on corporate value among listed companies in China. Second, this study evaluated the moderating effects of green production innovation and green craft innovation between ECSR and corporate value among these companies. Empirical analysis was conducted using panel data of the listed companies in China from 2015 to 2020. The results showed that the effects of the three ECSR dimensions (environmental production consciousness, eco-friendly production, and green management) on corporate value are statistically significant, but cannot be regarded as positive or negative. Green production innovation was found to moderate the effects of the three ESCR dimensions on corporate value. However, green craft innovation only exhibited a moderating effect between two ECSR dimensions and corporate value. This study’s findings fill the research gap in the fields of ECSR and enterprise green innovation and broaden the perspective of the sustainable development literature. The findings are also of great significance to the government for the implementation of environmental protection strategies and local economic development. Additionally, it is relevant to businesses in considering their environmental strategy.